Content and License Roaming for eHome DRM Applications - Zhu, Bin Benjamin; Li, Shipeng (IEEE Consumer Communications & Networking Conference (CCNC) Workshop on Digital Rights Management Impact on Consumer Communications, 2005)
In this paper, we provide a status report on our ongoing research project to develop a multimedia DRM system which provides seamless content and license roaming among devices for eHome applications. Fine granularity scalable video and audio codecs are selected to compress multimedia content for our multimedia DRM system. A compressed scalable stream is encrypted by our DRM system in such a way that an encrypted stream preserves fine granularity scalability so that protected content can be transcoded directly without decryption to meet target device’s characteristics. This fine granularity scalability of protected content is also very desired for eHome streaming applications when content is streamed from one device to other devices over a home wireless network since the bandwidth of a wireless network may fluctuate greatly, esp. when a device moves from one place to another. To facilitate easy license roaming among devices, a main home device such as PC is selected to act as a mini-license-server to issue restricted licenses to other devices according to the specified rights in the “main license” stored with the main device. Each “secondary device” has to be registered with the main device before a restricted license can be issued to it. There is a limit on maximum number of registered devices as well as on turnover rate. A restricted license is valid for a limited duration of time to allow a device to play protected content offline. Restricted license in a portable device has a longer duration than fixed devices to allow protected content to be played in a trip. Restricted licenses are synchronized periodically with the main license to ensure persistent rights management among allow all devices according to the specified rights in the main license.